PENGGUNAAN MODEL END USER SATISFACTION PADA PENILAIAN SISTEM INFORMASI PERPUSTAKAAN (OPAC) PERPUSTAKAAN STAIN JEMBER - Amelia, Vita (Jurnal Ilmu Budaya, 2012)
Information system is a combination of information technology and the persons who use the technology to support the operati on and management Asn an institution to provide and collect information, a library has important role as tools oflearning which provide information to the whole users. Dealing with that, this analysis aims to figure out the perception of the users on the usage of Online Public Catalogue (OPAC) in information system oflibrary in (SIPRUS) STAIN Jember. This analysis is study case analysis involving 3000 library members of STAIN Jember Iibraiy. It has 42 samples and questionaire is used and data is analyze d statitic ally by applying percentage test technique.